The political economy of the interior Gold Coast : the Asante and the era of legitimate trading, 1807-1875 - Hargrove, Jarvis L. (Lexington Books, 2015)
This book analyzes the Asante transition to legitimate commerce in the nineteenth century and highlights the political and economic relationships of the Asante state with surrounding African groups and European traders.